Pengaruh Profesionalisme, Etika Auditor, Pengalaman Kerja, dan Fee Audit terhadap Kualitas Audit pada KAP Medan - Wijaya, Larissa; Wijaya, Veronica; Katherin, Katherin (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2021)
In the process of obtaining the quality of a financial report, auditors are needed to master a good basis. This study includes respondents who are in the city of Medan. Due to the fact that the city of Medan has a number of KAPs on a relatively wide scale and demands that the presence of auditors be independent to carry out a review of the financial statements in presenting their views on the basis of the research, the participation in determining audit quality is representative enough for this research to be carried out. Professionalism, auditor ethics, work experience, and audit fees all have an impact on audit quality at the Medan KAP office. This research is quantitative and the data collection technique is by distributing questionnaires. The Medan Public Accounting Firm is the focus of the research demographics. In the following research, the number of auditors is 92 people. The data was tested using descriptive statistics, then tested the classical assumptions using normality, multicollinearity, heteroscedasticity and glesjer tests and hypothesis testing using multiple regression models assisted by IBM SPSS Statistics 22 software.Professionalism, work experience auditor ethics, and audit fees explain 17.5% of audit quality, and 82.5% are variables not described in this study.